Recommendations to improve wildlife exposure estimation for development of soil screening and cleanup values. (20th December 2013) - Sample, Bradley E; Schlekat, Chris; Spurgeon, David J; Menzie, Charlie; Rauscher, Jon; Adams, Bill; Fairbrother, Anne
ABSTRACT An integral component in the development of media‐specific values for the ecological risk assessment of chemicals is the derivation of safe levels of exposure for wildlife. Although the derivation and subsequent application of these values can be used for screening purposes, there is a need to identify the threshold for effects when making remedial decisions during site‐specific assessments. Methods for evaluation of wildlife exposure are included in the US Environmental Protection Agency (USEPA) ecological soil screening levels (Eco‐SSLs), registration, evaluation, authorization, and restriction of chemicals (REACH), and other risk‐based soil assessment approaches. The goal of these approaches is to ensure that soil‐associated contaminants do not pose a risk to wildlife that directly ingest soil, or to species that may be exposed to contaminants that persist in the food chain. These approaches incorporate broad assumptions in the exposure and effects assessments and in the risk characterization process. Consequently, thresholds for concluding risk are frequently very low with conclusions of risk possible when soil metal concentrations fall in the range of natural background. A workshop held in September, 2012 evaluated existing methods and explored recent science about factors to consider when establishing appropriate remedial goals for concentrations of metals in soils. A Foodweb Exposure Workgroup was organized to evaluate methods for quantifying exposure of wildlife to soil‐associated metals through soil and food consumption and to provide recommendations for the development of ecological soil cleanup values (Eco‐SCVs) that are both practical and scientifically defensible. The specific goals of this article are to review the current practices for quantifying exposure of wildlife to soil‐associated contaminants via bioaccumulation and trophic transfer, to identify potential opportunities for refining and improving these exposure estimates, and finally, to make recommendations for application of these improved models to the development of site‐specific remedial goals protective of wildlife. Although the focus is on metals contamination, many of the methods and tools discussed are also applicable to organic contaminants. The conclusion of this workgroup was that existing exposure estimation models are generally appropriate when fully expanded and that methods are generally available to develop more robust site‐specific exposure estimates. Improved realism in site‐specific wildlife Eco‐SCVs could be achieved by obtaining more realistic estimates for diet composition, bioaccumulation, bioavailability and/or bioaccessibility, soil ingestion, spatial aspects of exposure, and target organ exposure. These components of wildlife exposure estimation should be developed on a site‐, species‐, and analyte‐specific basis to the extent that the expense for their derivation is justified by the value they add to Eco‐SCV development. Integr Environ Assess Manag 2014;10:372–387. © 2013 SETAC